PERWALIAN TERHADAP ANAK HASIL NIKAH SIRI DALAM SISTEM BIROKRASI HUKUM PERNIKAHAN (Studi Kasus KUA Kecamatan Pujon 2021) - Agung Refa Nanda Putra; Samsyu Madyan; Moh. Muslim (Jurnal Hikmatina, 2021)
The status of children in family life is very important for the future of the child. In unregistered marriages, the status of children in state law or legislation is not clear or is considered a child born out of wedlock. In this study, researchers conducted research at the Ministry of Religious Affairs (KUA) Pujon District using a qualitative method (case study). The guardianship of daughters resulting from unregistered marriages in sharia can be represented directly by their biological fathers if the unregistered marriages are in accordance with the terms and conditions. However, in state law, children born out of unmarried marriages are considered the same as children born out of wedlock, so Article 43 paragraph 1 explains that children born out of wedlock only have a civil relationship with the mother and her mother's family. However, if the father wants to become a guardian and obtain legal rights for his child, the parents must submit an isbat marriage to the religious court